CHICK BEE'S CHARMING CHA-CHA - Han, Samantha; Lim, John (Singapore : Epigram Books, 2021)
The fun and furry characters are back with a lesson about staying true to oneself.Chick Bee has just learnt to do the cha-cha! She tries to wow everyone with her charming moves. But when her friends think her dance needs improving, Chick Bee doesn't know what to say. Will Chick Bee perform her cha-cha in her own charming way? Or will she listen to the advice of her friends? The Womps is a series about a bunch of friends who don't always get things right the first time.
Keywords: Readers; Self-confidence -- Juvenile fiction; Conduct of life -- Juvenile fiction